Diseño e implementación de un prototipo a láser para el etiquetado sobre cáscaras de frutos dulces. - Céspedes Navas, Richard Santiago (2018)
In the present project the elaboration of a prototype to laser for the labeling on the shell of sweet fruits is described, this process allows: to reduce the use of the plastic adhesives on the edible foods and to obtain the infomation on the origin of the product by means of the PLU Code (Price Look-Up). For the manufacture of the prototype, it was necessary to make previous drafts in AutoCAD, which helped to choose the most appropriate desing of the machine to later build it in different materials that satisfy and allow to make a laser labeling. Through the use of drivers, the movements of the laser machine were made. Also, taking as a reference the design of a CNC Shield V3, modifications were made that allowed the board to meet the needs presented by the laser prototype implementing such as: emergency stop, security for the physical part of the prototype, ignition indicators, laser power control, each of the systems allows the structure to function properly. For laser labeling on the fruit skin it is necessary to vectorize the image to be used, this is done through the free software “Inkscape”. The “CNC Control” program, which interprets the commands established in the “LaserGRBL”, is required for the movement of the motors. By performing 180 tests, it was posible to establish a 92.22% effectiveness of the prototype laser.